2005
DOI: 10.1258/0004563053026763
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of alpha-fetoprotein concentrations in cerebrospinal fluid of infants

Abstract: Background There are no published reference intervals for concentrations of alpha-fetoprotein (AFP) in the cerebrospinal fluid (CSF) of normal infants. The presence of abnormal concentrations of AFP in plasma or CSF may indicate the presence of a teratoma or a germ cell tumour with yolk sac elements. We measured CSF AFP in infants who did not have malignancy in order to determine its reference intervals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 14 publications
(15 reference statements)
0
13
0
Order By: Relevance
“…The serum levels of alpha-fetoprotein (AFP) were dramatically elevated in both patients. It was well known that serum AFP levels in newborns at birth was very high, with a reference interval of 15700–146,500 ng/ml and a medium value of 48,300 ng/ml [ 22 ], which then decreased dramatically with the increased age, and reached the childhood or adulthood reference range by around 6 weeks [ 23 ] to 8 months [ 24 ], and even by 3 years of age [ 25 ]. The age-dependant wide variation range of AFP levels indicated that there must be more than one unknown factor affecting the AFP serum level [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The serum levels of alpha-fetoprotein (AFP) were dramatically elevated in both patients. It was well known that serum AFP levels in newborns at birth was very high, with a reference interval of 15700–146,500 ng/ml and a medium value of 48,300 ng/ml [ 22 ], which then decreased dramatically with the increased age, and reached the childhood or adulthood reference range by around 6 weeks [ 23 ] to 8 months [ 24 ], and even by 3 years of age [ 25 ]. The age-dependant wide variation range of AFP levels indicated that there must be more than one unknown factor affecting the AFP serum level [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Five additional publications were retrieved from the references of those papers. A total number of 24 papers was therefore identified: 22 experimental studies [10,11,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] (one including two substudies [38]) and two abstracts from poster presentations [41,42]. The main features of the selected studies are reported in Table 1.…”
Section: Data Sources and Searchesmentioning
confidence: 99%
“…Looking at AFP concentrations alone could not reliably exclude tumors in infants, and often, histologic detection and imaging should be prioritized [5,8,9]. In general, there is an agreement about the low capability of AFP to rule out malignancy in preterm and term infants up to 4 months of age, as available upper reference limits (URL) look unreliable and unsuitable for clinical application [1,11]. Practical indications about the AFP use in young infants are therefore retrieved from literature based on registries/retrospective case series collected in years of clinical experience [12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Tumor markers have been identified for a variety of cancers and integrated into the diagnosis and management of patients with these cancers [17]. AFP is a 70 kDa glycoprotein normally secreted by the fetus primarily in the yolk sac, gastrointestinal tract, and liver [4, 5]. bHCG is a 36.7 kDa glycoprotein normally secreted by placental tissues [17].…”
Section: Introductionmentioning
confidence: 99%
“…Elevated serum or CSF concentrations of AFP are strong predictors of NGGCTs [7], as are high concentrations ob bHCG; however, the latter can be mildly to moderately increased in germinomas [7]. AFP is a 70 kDa glycoprotein normally secreted by the fetus primarily in the yolk sac, gastrointestinal tract, and liver [4, 5]. Since AFP concentrations normally drop to adult levels by 1 year of life, elevated levels in adolescents and adults can be indicative of malignancy [9].…”
Section: Introductionmentioning
confidence: 99%